2005
DOI: 10.1002/cncr.20840
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and follow‐up of patients with focal prostate carcinoma in 2 screening rounds after an interval of 4 years

Abstract: BACKGROUND Focal carcinoma detected by needle biopsy has been a common finding since prostate‐specific antigen (PSA)‐based screening was introduced. Clinicopathologic features in patients with focal prostate carcinoma who underwent radical prostatectomy (RP) or who were treated with watchful waiting (WW) were analyzed to detect clinical predictors for disease progression during follow‐up. METHODS Patients were selected from the European Randomized Screening study for Prostate Cancer. Focal carcinoma on sextant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
1
16
0
2
Order By: Relevance
“…The origin of the articles and clinical characteristics of the subgroups of patients with microfocal carcinoma are given in Table 1. Four studies reported on men who were diagnosed in the context of the European Randomized Trial for Screening of Prostate Cancer either in the Netherlands 11,21,47 or in Sweden. 44 Details of patient selection are provided in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The origin of the articles and clinical characteristics of the subgroups of patients with microfocal carcinoma are given in Table 1. Four studies reported on men who were diagnosed in the context of the European Randomized Trial for Screening of Prostate Cancer either in the Netherlands 11,21,47 or in Sweden. 44 Details of patient selection are provided in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-four articles 11,[15][16][17][18][19][20][21][22][23][24][25][26] addressed the specific question of the correlation between small-volume (''microfocal'') cancer on biopsy and pathologic findings, biochemical or clinical progression, or mortality, and 32 of those articles provided original data. 11,[15][16][17][18][19][20][21][22][23][24][25][26] Three of those articles were unique: One referred to the number of positive biopsy sites rather than cores, 42 another examined the relation between the number of positive cores on each side (right or left) and the incidence of extraprostatic spread on that side, 48 and the final article took into account both biopsy cancer volume and presenting PSA density in the presentation of results. 46 Those 3 articles were not considered further, because they did not provide data that were comparable with data from the other 29 articles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…small foci of <3 mm Gleason score 6 or lower prostatic adenocarcinoma in 1 biopsy (or in G€ oteborg teborg up to 2 adjacent biopsies 16 ), may be considered as an indirect parameter for the occurrence of small-sized low Gleason score prostate cancers in the screened population. 17 As this information is not recorded in the central database, the frequency of focal cancers was only available for the Rotterdam series, the reviewed Finnish cases and the previously published G€ oteborg cases. In Table III, the proportion of focal cancers during the 1st and 2nd screening in Finland, Rotterdam 17 and G€ oteborg 16 is shown.…”
Section: Resultsmentioning
confidence: 99%
“…For patients with clinically insignificant cancers, defined as organ-confined (pT2), no more than 10 mm in diameter and no more than Gleason score 6, 57 the option was discussed to include a separate comment in the report in order to point out that these tumors are rarely, if at all, associated with biochemical failure, provided that the surgical margins of the prostatectomy specimen are negative. 58 Consensus was obtained that, as a minimum requirement for the reporting of prostate cancer in radical prostatectomy specimens, some quantitative estimate of cancer volume should be undertaken, the nature of which being dependent on routine practice within the pathology laboratory (Table 3). It was recommended that each laboratory should adopt a well-defined and standardized protocol and that this be used by all pathologists within the institution who report radical prostatectomy specimens.…”
Section: Measurement Of Tumor Volumementioning
confidence: 99%